2017
DOI: 10.1038/srep42384
|View full text |Cite
|
Sign up to set email alerts
|

Feature-based attentional weighting and spreading in visual working memory

Abstract: Attention can be directed at features and feature dimensions to facilitate perception. Here, we investigated whether feature-based-attention (FBA) can also dynamically weight feature-specific representations within multi-feature objects held in visual working memory (VWM). Across three experiments, participants retained coloured arrows in working memory and, during the delay, were cued to either the colour or the orientation dimension. We show that directing attention towards a feature dimension (1) improves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
62
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 56 publications
17
62
4
2
Order By: Relevance
“…Finally, it is noteworthy that the vast majority of studies linking attention to WM (as well as alpha to attention) regard spatial‐based prioritisation mechanisms. It has recently been shown that visual feature dimensions (such as orientation and colour of all items in the array) can also be dynamically up‐ and downregulated during visual WM retention (Ye et al ., ; Niklaus et al ., ). Whether alpha modulations also support such feature dimension‐based attentional prioritisation (as reported for the perceptual domain; see Snyder & Foxe, ), remains an interesting target for future research.…”
Section: Attenuated Alpha States Reflect Behaviourally Relevant Priormentioning
confidence: 97%
“…Finally, it is noteworthy that the vast majority of studies linking attention to WM (as well as alpha to attention) regard spatial‐based prioritisation mechanisms. It has recently been shown that visual feature dimensions (such as orientation and colour of all items in the array) can also be dynamically up‐ and downregulated during visual WM retention (Ye et al ., ; Niklaus et al ., ). Whether alpha modulations also support such feature dimension‐based attentional prioritisation (as reported for the perceptual domain; see Snyder & Foxe, ), remains an interesting target for future research.…”
Section: Attenuated Alpha States Reflect Behaviourally Relevant Priormentioning
confidence: 97%
“…Information regarding the relevance of some features over others may become available, however, only after the objects were already encoded to WM. A handful of recent studies have also investigated whether people can selectively weight features already encoded to WM, or in other words, whether they can "ignore" irrelevant features in WM [10,29,30]. In these studies, participants encoded a set of multifeatured objects (e.g., colored and oriented gratings).…”
Section: Attending To Different Featuresmentioning
confidence: 99%
“…In a typical retro-cue experiment, after presentation of a memory array, a cue identifies the location of one item that is most likely to be tested in a subsequently following recognition test. A validly retro-cued item can be accessed faster and more accurately in comparison to conditions where no cue, or an uninformative cue, is provided (Griffin & Nobre, 2003;Niklaus, Nobre, & van Ede, 2017;Rerko & Oberauer, 2013;Souza, Rerko, Lin, & Oberauer, 2014;Souza, Rerko, & Oberauer, 2016, 2014van Ede, Niklaus, & Nobre, 2016).…”
Section: Introductionmentioning
confidence: 99%